Contribution of project managers' capability to project ending performance under stressful conditions. Issue 2 (April 2019) - An, Nan; Qiang, Maoshan; Wen, Qi; Jiang, Hanchen; Xia, Bingqing
Abstract: Project ending phase is strategically important for organizations, but it has been largely neglected in previous research and practice. In this phase, the project manager is the executor of strategic moves and plays a paramount role in completing projects efficiently and other summarizing work, but the issues related to complicated work content, future career path, and work-family conflicts may rapidly increase the pressure on project managers at the same time. These stressors affect project managers psychologically, physiologically, and behaviorally and inhibit project managers' capability from functioning well. Under this scenario, the purpose of the study is to empirically figure out the impact of project managers' participation in project ending, and their capability's contribution to project ending performance under pressure. This research identified six factors of project ending stressor, namely skill discretion, decision authority, job demands, job insecurity, job readjustment, and family support. A sample of 214 experienced project managers from different industries was collected, and structural equation modeling (SEM) was used. The results show that project managers play as coordinators among stakeholders in completing product handover and accumulating knowledge asset, thus indirectly enhancing organizational strategic value integration in project ending. Completing product handover is more efficient in terms of strategic integration than accumulating knowledge assets. When the stressors begin to pile up, the contribution of project managers' capability will be hindered, but only the process of accumulating knowledge assets is affected. Thereby, project managers under pressure tend to first lose control of the task with less strategic importance. This study supplements insights to related theory in project management and human resource management fields and also provides practical suggestions for project management and personnel management in project-based organizations. Highlights: We develop the content and scale of a domain-specific construct, project ending stressor. We test the reliability and validity of the newly-designed scale based on a sample of 214 experienced project managers. We test the inhibition effect of project ending stressor to project manager's capability on project ending performance. Several practical implications for project management and organizational human resource management are included.